Responsibilities and Legal Protection for Substitute Notaries for Authentic Deeds They Have Made - Yansyah, Dedi; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
A Substitute Notary is someone who is temporarily appointed as a Notary to replace a Notary who is on leave, sick, or temporarily unable to carry out his or her position as a Notary with the aim of ensuring that there is no vacancy in carrying out the duties of the Notary. This research aims to 1) Find out and analyze the Responsibility and Protection for Substitute Notaries for authentic deeds they have made and 2) Find out and analyze the legal consequences for the responsibilities and protection for Substitute Notaries who have issued authentic deeds. This research approach uses a Nomative Juridical approach with the research specifications in writing this thesis being analytical descriptive, especially in terms of responsibility and legal protection for Substitute Notaries for the authentic deeds they make. The type of research is qualitative and the data source comes from primary data and secondary data. The conclusions in this research show that in accordance with Article 65 of the Notary Position Law, a Substitute Notary is responsible for the formal form of the Authentic Deed. The responsibilities of a Substitute Notary can be divided into two, namely, responsibilities while still serving as a Notary and responsibilities when no longer serving as a Notary. Legal Protection for Substitute Notaries according to Article 66 of the Notary Position Law, namely through the Honorary Council of Notaries, the Rights and Obligations of Denial, Attaching Letters, Documents and fingerprints to the Deed Minutes, Organization of the Indonesian Notary Association, Supervision of the implementation of the Notary's code of ethics. The legal consequences for the responsibilities and legal protection of a Substitute Notary can be divided into three: (1) civil legal consequences, namely compensation for losses; (2) Administrative legal consequences, namely verbal warning, written warning, temporary dismissal, honorable dismissal and dishonorable dismissal; (3) criminal legal consequences, a Substitute Notary can be punished if he violates the provisions regarding falsification of an authentic deed, provides false information in an Authentic Deed and reveals secrets which he is obliged to keep because of his position. Keywords: Authentic; protection; Responsibility; Substitute.